Structural and modal analysis of hybrid low altitude self-sustainable surveillance drone technology frame. (2021) - Sundararaj, S.; Dharsan, K.; Ganeshraman, J.; Rajarajeswari, D.
Abstract: Structural and modal analysis of different versions of a special type of drone frame using carbon fibre and ABS materials are carried out in this paper using commercially available simulation software. The drone discussed in this paper is capable of self-sustaining in terms of power by generating its energy from solar cells and using a chamber filled with lighter than air materials. Thus, to support the drone and its components for such applications four versions of the frame namely directly connected triangular frame, short armed semi-circular frame, long armed semi-circular frame and short armed rectangular frame with two different materials such as carbon fibre and Acrylonitrile Butadiene Styrene (ABS) plastic were analysed by static structural and frequency analysis. The maximum permissible stress, strain displacement and frequency values were obtained from the simulation. The analysis indicates that the directly connected triangular frame and long armed semi-circular frame have less strength compared to other two versions but the frames can be manufactured easily. Whereas short armed semi-circular frame and short armed rectangular frames are complex to manufacture but they have high strength to withstand the induced stress.